The Impact of Capital Structure and Profitability on Company Value - Heni, Frederika Prihantini; Utami, Endang Sri (Research Horizon, 2025)
This study aims to investigate the effects of return on assets and the debt-to-equity ratio on the value of manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The price-to-book value ratio is used to determine a company’s value. This research employs a quantitative method using multiple linear regression analysis. The sample includes 67 companies selected through purposive sampling techniques. The hypothesis testing results show that both the debt-to-equity ratio and return on assets have a significant and comprehensive effect on firm value. Furthermore, the results indicate that the debt-to-equity ratio and return on assets together have a notable impact on the company's value. The coefficient of determination shows that these two independent variables account for only 34% of the variation in firm value, with the remaining 66% influenced by other unexamined factors. This study provides insights for businesses and investors regarding the importance of financing strategies and operational efficiency in enhancing firm value, especially during the economic recovery following the pandemic. Therefore, future researchers are advised to include additional variables to obtain more comprehensive and conclusive results.